Metabolic Syndrome and Lifestyle - Mohammadhosien Bayazi; Alireza Rajaei; Ali Delshad Noghabi (Gonabad University of Medical Sciences, 2020)
Dear Chief in Editor Metabolic syndrome (MetS), places an individual at risk for type 2 diabetes (T2D), cardiovascular disease (CVD) and other related medical problems, including fatty liver, cholesterol gallstones, polycystic ovary syndrome, obstructive sleep apnea and gout [1]. MetS is becoming a worldwide epidemic as a result of the increased prevalence of obesity and a sedentary lifestyle, and the prevalence of MetS in the adult population is relatively high. Four elements comprising MetS have been identified: central obesity, dyslipidemia (increased triglycerides and reduced high density lipoprotein (HDL) cholesterol), hypertension, and glucose intolerance; however, the definitions used vary somewhat between ethnic groups. The National Cholesterol Education Program Adult Treatment Panel (ATP III ) defined MetS as the presence of three or more of the following conditions: Abdominal obesity as waist circumference (WC) ≥102 cm for males or ≥88 cm for females (In Iran according to the guidelines of the Nutrition Improvement Office of the Ministry of Health and Medical Education, waist circumference ≥90 cm for men and women), systolic/diastolic blood pressure (SBP/DBP) ≥130/85 mmHg or treatment of previously diagnosed hypertension ( HTN), fasting blood glucose level ≥100 mg/dl or previously diagnosed T2D, HDL level less than 40 mg/dl in men and less than 50 mg/dl in women or specific treatment for this lipid abnormality , triglyceride level ≥150 mg/dl or specific treatment for this lipid abnormality [1,2].  Some probable dietary risk factors, such as high intakes of saturated fatty acids and low intakes of omega‑3 fatty acids also increase the risk of cardiovascular disease. In addition, inadequate physical activity, smoking and extreme alcohol consumption have been linked with increased risk of central obesity and other metabolic abnormalities. Smoking and physical inactivity have been identified as important modifiable risk factors for MetS and its consequences. Several studies have shown that smoking is considered as a major risk factorfor CVD and TD2 and it is also associated with metabolic abnormalities and increases the risk of MetS. Sedentary physical activity is one of the major modifiable risk factors for the MetS. The second leading cause of premature morbidity and mortality is excess body weight gain due to high calorie diet and insufficient physical activity. Physical activity is associated with many health-related benefits, including a reduced risk of developing several chronic diseases such as obesity, CVD, TDM, and MetS. The adverse effect of physical inactivity on MetS components is thought to be due to reduced energy expenditure which results in increased energy intake. Cross-sectional studies reported an inverse association between physical activity and MetS. Most of the guidelines support that at least 150 minutes of moderate-intensity physical activity per week could be associated with a lower prevalence of MetS [3[. Many studies were conducted to examine the dietary patterns that may be associated with MetS and its components. One of the dietary patterns that are known to be associated with reducing MetS is the Mediterranean Diet. The Mediterranean diet was fist defined as the diet usually consumed among the populations bordering the Mediterranean Sea. It is characterized by the consumption of fruit, vegetables, nuts, olive oil, fish and low consumption of saturated fat, red meat, processed meat, refied carbohydrates, and whole fat dairy products. Adherence to the Mediterranean Diet improves both physical and mental health and improves quality of life. Also, it has been revealed that Mediterranean Diet may lower the risk of having elevated low-density lipoprotein cholesterol (LDL), blood glucose values, and TG, and improves HDL levels. Diets rich in antioxidants (vitamin E, vitamin C, and β-carotene) exert beneficial influences on glucose metabolism and diabetes prevention. They are also associated with a   reduction in the risk of developing CVD. Dietary fiber intake especially from cereals and whole grains can manage and affects body weight, blood glucose and lipid profile [4]. Stress Management is useful for preventing of MetS. The increased cortisol production in chronic stress may lead to having higher WC which results in accumulation of abdominal fat. In addition to the hormone disturbance; it has been shown that endothelial dysfunction and its related arterial compliance reduction were more serious in stressful persons. A healthy lifestyle including weight loss through calorie restriction, healthy food choices, increased physical activity and smoking cessation has a remarkable role in preventing or delaying the onset of MetS or treating the condition when present. Lifestyle interventions such as diet and physical activity would be the first line approach for improving the metabolic risk factors related to cardiovascular disease. Participants should be recommended to consume less junk foods, high amount of fruits, and vegetables and also encouraged to do moderate level of physical activity (e.g., jogging, brisk walking, swimming, yoga, and bicycling) for 40-45 min at least 5 times in a week. In conclusion, classic healthy lifestyle habits have proven to reduce the risk of developing MetS.